Efficient characterization of phase modulator based on Lyot-Sagnac interferometer. (31st March 2023) - Yu, Aodi; Huang, Yuhao; Xia, Li
Abstract: An effective method for evaluating the performance of an electro-optic phase modulator (EOPM) based on the Lyot-Sagnac interferometer is presented and experimentally demonstrated. The Sagnac loop is made up of an EOPM with polarization-maintaining fiber (PMF) pigtails and a length of PMF, which serves as the reference segment. The reference PMF contributes to catalyzing the Vernier effect and magnifying the measurement sensitivity. In order to obtain a better spectrum, numerical investigations are carried out to optimize the parameters in the structure. The experimental results validate the theoretical simulation and display that the envelope of the output spectrum will shift significantly with increasing the modulation voltage. The measurement sensitivity is estimated to be −5.2271 nm/V with linear fit index R 2 up to 0.9965 which is amplified by about 87.25 times compared to that of the single Sagnac interferometer. And the measured half-wave voltage and modulation index of the EOPM are around 3.61 V and 0.87 rad/V, respectively. The entire structure is constructed with optical fiber, which is extremely compact and can be extended to plug-and-play scheme for more practical applications.